Проблема виховання молоді: соціально-філософський аспект - Тоцький, Ігор (Видавництво Львівської політехніки, 2012)
В статье религиозно-философская проблема спасения человеческой души рассматривается как ключевая педагогическая проблема. На принципах Библейской сотериологии (науки о спасении), трансформированной в философию спасения, выстраиваются организационно-методические основания педагогики спасения и сотериологического воспитания, которое по мысли автора должно занять ведущее и важное место в системе украинского просвещения на ряду с церковным и домашним (семейным) воспитанием. The article considers religious and philosophical problem of a human salvation to be a key pedagogical problem. On the principles of the Biblical Soteriology (the science about redemption), transformed into philosophy of salvation, organizational and methodical principles of the pedagogy of salvation and soteriological education are formed up, which, in the author’s opinion, must hold leading and important place in the system of Ukrainian education alongside of church and family education.
Проблема воспитания молодежи: социально-философский аспект
The problem of the youth education: social and philosophical aspect
Keywords: социально-философский аспект; философия спасения; сотериологическое воспитание; педагогика спасения; зона спасения; зона греха; social and philosophical aspect; philosophy of the salvation; soteriological education; pedagogy of the salvation; zone of the salvation; zone of the sin